Study of Drug-Drug and Drug-Food Interactions of Mesalazine Through FTIR and DSC - Alam, Md Mahbubul; Tasneem, Faria; Kabir, AK Lutful; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2019)
A well-established drug used in the management of inflammatory bowel disease is 5-aminosalicylic acid (e.g. Mesalazine or Mesalamine). For the treatment of mild to moderate flares of ulcerative colitis and Crohn’s disease, Mesalazine has been used as the first line drug in both western and Asian countries due to its superiority over other drugs in terms of side effects and toxicities. Besides, some other drugs are also prescribed for total resolution of different symptoms of ulcerative colitis and associated diseases, which include Acetaminophen, Metronidazole and Vitamin D3. Moreover, physicians instruct that Mesalazine should be taken at least one hour before meal. So, there are enough scopes of studying the drug-food interaction of Mesalazine to assess if there is any incompatibility present with food. Thus, in the present study, Mesalazine and physical mixtures of Mesalazine (1:1) in solid form along with the aforementioned drugs were prepared and analyzed to evaluate the compatibility among them using Fourier Transform Infrared Spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC). In addition, interactions of Mesalazine with food stocks such as chicken and vegetable broth, fruit juice, milk and soybean oil were studied using FTIR, considering these as the common sources of protein, vitamin, fiber, minerals and fat. From this study, it was interpreted that, major interactions of Mesalazine were present with food samples. Besides, FTIR and DSC data revealed subtle clues of incompatibilities between Mesalazine and the other two drugs except Vitamin D3. So, the results may prove to be useful for related research works in future Dhaka Univ. J. Pharm. Sci. 18(2): 257-269, 2019 (December)